A157 THE THRESHOLD FOR INFLIXIMAB TROUGH LEVELS LEADING TO DOSE ESCALATION DIFFERS BETWEEN CROHN'S DISEASE AND ULCERATIVE COLITIS. (1st March 2018) - Cookson, T A; Fedorak, R; Halloran, B P; Dieleman, L A; Wong, K; Huang, V; Peerani, F; Kroeker, K I
Abstract: Background: Therapeutic drug monitoring (TDM) of infliximab (IFX) provides an objective measure that allows physicians to optimize the dose for patients on biologic therapies and potentially reduce loss of response (LOR). The currently accepted therapeutic range is 3 – 7 μg/mL. With the potential for LOR with low drug levels and the high cost of IFX, it is important to manage medications efficiently. To better understand how physicians at the University of Alberta Hospital are using TDM, we conducted a retrospective chart review to see the clinical decisions made in response to TDM. Major clinical decisions include: no change, dose escalate (increase in dose or shorten interval), reload (2 extra doses 2 weeks apart), or dose de-escalate (decrease in dose or lengthen interval). Aims: To measure the proportion of IFX trough levels that lead to a clinical change in therapy and compare how the cut-offs used to change therapy vary by disease type. Methods: This is a retrospective chart review of all IBD patients (17+ years) on IFX at the University of Alberta IBD Clinic who had at least one trough level measured between 2015 and 2017. Charts were reviewed for demographic data, TDM drug levels, and any clinical decisions relating to the drug levels. Numerical data and categorical data are presented as a mean (standard deviation) and proportions, respectively, using t-tests and Chi-squared tests. Statistical significance is assessed at p<0.05. Results: The information of 758 drug levels was collected from 402 patients. Demographic data for the drug levels included: 51.7% male; 72.1% Crohn's disease; mean age of 38.9 (±14.8). 54.5% of all levels had the patient on concomitant immunosuppressants. Of all trough levels, 344 (45.4%) led to a clinical change in therapy. A majority (52.7%) of trough levels that had an elevated fecal calprotectin (FCP) of >250μg/g led to a dose escalation (p<0.001). Drug levels with positive IFX antibodies (ATIs) correlate to switching to a new biologic (p=0.042) where the mean ATI level was 3.00 (3.39). Table 1 shows the mean IFX level for clinical changes made by disease type. Conclusions: Physicians at the University of Alberta IBD Clinic use FCP, a therapeutic range of ~3 – 14 μg/mL, and the presence of antibodies as major factors in making clinical changes in IFX therapy for patients with IBD. Cut-offs used to reload and dose escalate are significantly higher in UC patients compared to CD patients. Funding Agencies: Department of Medicine Clinical Research and Projects Studentship Grant